PENGARUH MANAJEMEN KEPALA SEKOLAH, PENGALAMAN MENGAJAR DAN KOMUNIKASI TERHADAP KINERJA GURU SMP NEGERI DI KECAMATAN KOTA JUANG KABUPATEN BIREUEN - Haryadin; Zainuddin (JURNAL KEBANGSAAN, 2023)
This study aims to analyze the effect of principal management, teaching experience and communication on the performance of State Middle School teachers in Kota Juang District, Bireuen Regency. With a descriptive and associative analysis approach to the path analysis model. The number of respondents was 168 teachers. The results of the analysis show, 1) There is a direct and indirect effect of principal management on the performance of State Middle School teachers in Kota Juang District, Bireuen Regency, amounting to 62.52%. 2) There is a direct and indirect effect of teaching experience on the performance of state junior high school teachers in Kota Juang District, Bireuen Regency, amounting to 31.08%. 3) There is a direct and indirect effect of communication on the erformance of state junior high school teachers in Kota Juang District, Bireuen Regency, amounting to 31.26%. 4) Simultaneously the principal management factors, teaching experience and communication have a significant effect on teacher performance by 56.4%.